Tiktok Platform Opportunity: How Does it Influence SMES Brand Awareness among Generation Z? - Genoveva Genoveva (Faculty of Economics, Universitas Sriwijaya, 2021)
The increasing of social media and digital-based business, transforms traditional marketing into interactive marketing, where consumers can interact directly with brands. TikTok as one of the popular social media among Generation Z also contributes to SMEs brand awareness. This study aims to measure the role of content marketing, influencers and psychological factors on brand awareness of SMEs from the perspective of Generation Z. This study uses a quantitative approach, with a questionnaire as a data collection tool. With snowball sampling, the targeted respondents reached 238 people. The data is then processed with SPSS version 25. The results showed that content marketing, influencers and psychological factors had a positive and significant effect on brand awareness. However, the factor that has the greatest influence on brand awareness is content marketing (63.5%), followed by psychological factors 34.2% and influencers only 21.6%.